Accountability and transparency in emerging countries: Governance, democratic currents and change. (11th November 2021) - Samaratunge, Ramanie; Alam, Quamrul
Abstract: Accountability and transparency are evolving challenges to governance and public administration in a highly complex global governance system. It is a difficult challenge in the emerging economies due to a significant deficit in democratic policy and institutional effectiveness. Few will discount the seemingly insurmountable challenges emerging economies face, whether these be economic, social inequality or social transformation. In light of these issues, accountability has been compromised or even neglected. We no sooner settle on a prescription for redress of governance and behavioural deficits than conditions in the world around us change, necessitating yet another round of reflection, analysis and policy development. This introduction to the Special Issue summarises and highlights some of the most salient features of accountability, transparency and governance capability confronted by public administration systems in emerging economies. Countries are faced with the need to make choices about their institutions and their actions within the broader framework of improving service delivery within a highly internationalised public administration system. Choices are made based on capacity, history and politics. These issues are by their nature contentious and contested, and it is no bad thing that this should be so, because out of contest come lessons about future choices and actions.